Ovarian goiter with papillary thyroid carcinoma: A very rare case - Puja Agung Antonius; Dr. dr. Syamel Muhammad, SpOG(K)-Onkogin; Muhammad Zaldy Rasyid Putra; Santy Saberko (Universitas Andalas, 2022)
Struma ovarii is a rare condition, in which thyroid tissue is the predominant element in an ovarian carcinoma. Thyroid tissue may demonstrate the same spectrum of pathological features as in the normal thyroid including benign and malignant changes. The malignant type is very rare, only 5% from all incidents of goiter ovarii. We present a case of papillary thyroid carcinoma arising in a struma ovarii of the right ovary in a 43-year-old female